Antidiabetic potential of phytochemicals isolated from the stem bark of Myristica fatua Houtt. var. magnifica (Bedd.) Sinclair. Issue 12 (23rd July 2018) - Prabha, B.; Neethu, S.; Krishnan, S. Lekshmy; Sherin, D.R.; Madhukrishnan, M.; Ananthakrishnan, R.; Rameshkumar, K.B.; Manojkumar, T.K.; Jayamurthy, P.; Radhakrishnan, K.V.
Graphical abstract: Highlights: A novel compound along with six acyl phenols are isolated from M. fatua stem bark. All the compounds displayed significant α-glucosidase inhibitory activity. Malabaricone C binds the pocket of N-terminal human maltase glucoamylase. Malabaricones A, B and C exhibited potent antiglycation property. Malabaricone B significantly enhances the glucose uptake in L6 myotubes. Abstract: Phytochemical investigation of the stem bark of Myristica fatua Houtt. led to the isolation of a new compound 1 (3-tridecanoylbenzoic acid), along with six known acylphenols (2 –7 ). All the compounds displayed moderate inhibitory activity on α -amylase and significant activity on α -glucosidase; however malabaricone B (6 ) and C (7 ) were identified as potent α -glucosidase inhibitors with IC50 values of 63.70 ± 0.546, and 43.61 ± 0.620 µM respectively. Acylphenols (compounds 3 –7 ) also showed significant antiglycation property. The molecular docking and dynamics simulation studies confirmed the efficient binding of malabaricone C with C -terminus of human maltase-glucoamylase (2QMJ ). Malabaricone B also enhanced the 2-NBDG [2-(N-(7-nitrobenz-2-oxa-1, 3-diazol-4-yl)amino)-2-deoxy glucose] uptake in L6 myotubes. These findings demonstrate that acylphenols isolated from Myristica fatua Houtt. can be considered as a lead scaffold for the treatment of type II diabetes mellitus.